Viral and atypical bacterial etiologies of severe acute respiratory infection (SARI) in Egyptian patients: epidemiological patterns and results from the sentinel surveillance study 2010–2014 - Ashraf M Hatem; Usama E Abuelhassan; Sherif A.A Mohamed; Magda S Rizk; Amany El-kholy; Mohamed Al-Harras (Egyptian Journal of Chest Disease and Tuberculosis, 2019)
Background Respiratory viral and atypical bacterial infections data in Egyptian patients are sparse. This study described the epidemiological pattern of viral and atypical bacteria as causes for severe acute respiratory infections (SARI) in hospitalized patients in Egypt. Patients and methods SARI surveillance was carried out at a Teaching University Hospital during the period 2010–2014. All hospitalized adults and pediatric patients meeting the WHO case definition criteria for SARI were enrolled. Nasopharyngeal/oropharyngeal swabs were collected and samples were tested using reverse transcription-PCR for influenza A, B, respiratory syncytial virus, human metapneumovirus, parainfluenza viruses 1, 2, 3, 4, adenovirus, human bocavirus, coronavirus, enterovirus, rhinovirus, and atypical bacteria (Mycoplasma spp., Chlamydia spp., and Legionella spp.). Results Overall, 1075/3207 (33.5%) cases had a viral etiology, and included 912 (84.4%) women and 163 (15.6%) men, with a mean age of 5.74±13.87 years. The highest rates were reported for respiratory syncytial virus (485 cases, 45.2%), parainfluenza virus (125, 11.6%), and adenovirus (105, 9.8%). Single viral etiology was reported in 901 (83.3%), while 174 (16.7%) cases had multiple etiologies. Children had a higher rate (981, 91.2%) compared with 94 (8.8%) cases in adults. Only three and one cases were positive for Mycoplasma spp. and Chlamydia spp. infections, respectively. Neither coronavirus nor Legionella spp. were detected. Conclusion Viral infections were encountered in one-third of hospitalized Egyptian adult and pediatric patients with SARI. Atypical bacteria had a minor role in SARI in our locality. Ongoing surveillance programs will better describe the epidemiology of SARI and will provide specific data to enable decision makers to take appropriate prevention measures.